Team leadership - Holzknecht, James; Castalia Media (Firm); Insight Media (firm) ([S.l.] : Castalia Media ; New York, NY : Distributed by Insight Media, 2007)
This program examines the key components to developing team leadership. The program utilizes scenarios to illustrate important points and it faetures some of the top team building leaders from around the city
Title from title screen
Team leadership experts: Michelle Akers, Tom Flick, Dennis Goin, Hugh Graham, Don James, Sharon Parker, Carol Tait, George Takei, Paula Washington
Keywords: Leadership; Teams in the workplace; Social groups